2015
DOI: 10.1097/md.0000000000000585
|View full text |Cite|
|
Sign up to set email alerts
|

The High Prevalence of Hypovitaminosis D in China

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 29 publications
9
76
5
1
Order By: Relevance
“…[47][48][49] The reverse phenomenon has been reported in Finland where advancing age has been associated with higher 25-(OH) D values in both sexes up to the age of 80 and was attributed to an "active pensioner" outdoor lifestyle, increased consumption of fatty fish, as well as dairy product fortification and VitD supplement use. 20,50 Consistent with previous studies, 20,38,40,[51][52][53][54] 25-(OH) D levels in females were found to be lower compared to males, up to the age of 50 years; thereafter the levels of 25-(OH)D were not different from those of males. A plausible explanation might include VitD and calcium supplementation in post-menopausal women together with changes in circulating estrogen levels, as well as lifestyle factors not addressed in this study (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…[47][48][49] The reverse phenomenon has been reported in Finland where advancing age has been associated with higher 25-(OH) D values in both sexes up to the age of 80 and was attributed to an "active pensioner" outdoor lifestyle, increased consumption of fatty fish, as well as dairy product fortification and VitD supplement use. 20,50 Consistent with previous studies, 20,38,40,[51][52][53][54] 25-(OH) D levels in females were found to be lower compared to males, up to the age of 50 years; thereafter the levels of 25-(OH)D were not different from those of males. A plausible explanation might include VitD and calcium supplementation in post-menopausal women together with changes in circulating estrogen levels, as well as lifestyle factors not addressed in this study (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…In a study in Chinese adults, Yu et al . reported that vitamin D status was affected by living in a coastal or inland region, rather than living in regions of different latitudes; they suggested that inland residents might have had lower vitamin D status because of lower fish oil consumption . In the present study, however, Tochigi Prefecture is an inland region, whereas Fukuoka and Kumamoto Prefectures are coastal regions.…”
Section: Discussioncontrasting
confidence: 62%
“…In China, the prevalence of serum 25OHD 3 deficiency is higher than 50% in all age groups [25,26], reaching 85.8%, 97%, and 89.7% in schoolaged students, adolescents, and adults, respectively, in some remote and low-income regions [27][28][29]. The prevalence of vitamin D deficiency in schoolchildren (ages 7 to 11 y) is 56.4% in 2013 [30] and 45.85% of (ages 1 to 10 y) [31] in Harbin.…”
Section: Discussionmentioning
confidence: 99%